Pengaruh work overload dan work life balance terhadap job performance melalui job stress pada karyawan kantor pelindo terminal petikemas bjti - Zerlina, Aneilah Vivian; Budiono (Universitas Negeri Surabaya, 2024)
This research will discuss job performance, work overload, work-life balance, and job stress influence. So that job performance is always consistent and the organization pays attention to work issues. Performance has a broader meaning, not only stating the results of work but also how the work process takes place by the performance standards set by the company. This research is causality research with a quantitative approach. The sampling technique uses nonprobability sampling with purposive sampling, where the researcher has determined the sample with certain considerations and a total of 80 respondents at container terminal company in Surabaya. The statistical analysis used in this research is Partial Least Squares (PLS) with the help of SmartPLS 4.0.9 software. This research examines and analyzes the influence of work overload and work-life balance on job performance through job stress in Pelindo office employees atcontainer terminal company in Surabaya. This research is causality research with a quantitative approach. Tthe sample with specific considerations and a total of 80 respondents at container terminal company in Surabaya. The results of this research explain that work overload has a positive and significant effect on job performance and stress. Work-life balance does not affect job performance. Work-life balance has a positive and significant impact on job stress. Job stress has a positive and significant effect on job performance. Job stress does not mediate the impact of work overload on job performance. Job stress mediates the influence of work-life balance on job performance.